Gender-Based Family Approach: Causes and Factors of Gender Inequality in Family Life - Alice Ayawine; Mtebi Nkrabia Gmaligan; Joseph Ayamga Awimboora (Journal of Gender and Millennium Development Studies, 2026)
Background: Gender role inequality within the family is shaped by gender discourse that is legitimised through cultural norms and everyday practices, where domestic responsibilities are often perceived as “natural” obligations of women, placing them in subordinate roles. Objective: This study aims to analyse the factors that construct women’s role inequality in families and to explore the processes of negotiation and transformation in gender relations through the Gender Model Family approach. Method: A qualitative design grounded in Gender Discourse Analysis was employed. Data were collected through in-depth interviews and focus group discussions to examine narrative patterns, social legitimacy, and power dynamics within family life. Result: Findings show that gender inequality is maintained through traditional discourse and social pressures that normalise male dominance in family roles. However, emerging negotiations between family members foster more cooperative domestic practices and participatory decision-making, indicating a gradual transformation in gender relations. Conclusion: The family operates as a dynamic arena in which gender norms are both reproduced and reconstructed through continuous interaction and meaning negotiation, leading to more equitable and adaptive relationships. Contribution: This study advances the Gender Model Family framework by providing a discourse-based understanding of how gender inequalities are constructed and transformed, offering implications for promoting more egalitarian family relationships